Epigenetic age acceleration, neonatal morbidities, and neurobehavioral profiles in infants born very preterm - Uriel Paniagua; Barry M. Lester; Carmen J. Marsit; Marie Camerota; Brian S. Carter; Jennifer F. Check; Jennifer Helderman; Julie A. Hofheimer; Elisabeth C. McGowan; Charles R. Neal; Steven L. Pastyrnak; Lynne M. Smith; et al. (Epigenetics, 2023)
ABSTRACTEpigenetic age acceleration is a risk factor for chronic diseases of ageing and may reflect aspects of biological ageing. However, few studies have examined epigenetic ageing during the early neonatal period in preterm infants, who are at heightened risk of developmental problems. We examined relationships between neonatal age acceleration, neonatal morbidities, and neurobehavioral domains among very preterm (<30 weeks gestation) infants to characterize whether infants with early morbidities or different neurobehavioral characteristics had accelerated or decelerated epigenetic ageing. This study uses data from the Neonatal Neurobehavior and Outcomes in Very Preterm Infants (NOVI) study, restricted to infants with data on variables assessed (n = 519). We used generalized estimating equations to test for differences in age acceleration associated with severe neonatal medical morbidities and neurobehavioral characteristics. We found that infants with neonatal morbidities, in particular, bronchopulmonary dysplasia (BPD), had accelerated epigenetic age – and some evidence that infants with hypertonicity and asymmetric reflexes had increased and decreased age acceleration, respectively. Adjustment for gestational age attenuated some associations, suggesting that the relationships observed may be driven by the duration of gestation. Our most robust finding shows that very preterm infants with neonatal morbidities (BPD in particular) exhibit age acceleration, but most neonatal neurobehavioral characteristics and morbidities are not associated with early life age acceleration. Lower gestational age at birth may be an upstream factor driving these associations.